(Re) negociação das Identidades Sociais nas aulas de Produção Textual no 5º ano do Ensino Fundamental - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Considering current social demands, working textual production with Elementary School students from the 5th grade, through literacy practices developed in Portuguese Language classes, looking at re-negociation of social identities, is a “task” to be thought and improved by teachers. This way, this research aims at investigate how the students from the 5th grade of Elementary School re-negociate their identities in writing productions through literate practices and literacy events developed in Portuguese Language classes. For this, it were elected two groups of a public school in Ponta Grossa/PR, in the second semester of 2016, and, in this ethnographic insertion, data were generated through observations and also through textual productions developed by those students. Thus, the study is carried within literacy concepts of dialogism, wording, speech genres, writing production at school and also issues about subject and identity. Data were analyzed in light of Bakhtin studies, considering dialogical relations, and authors who guide concepts about literacy(ies) and identity(ies). Besides, this investigation is based on official documents of Elementary School in national and municipal level. The research participants were 13 students of Group A and 9 from Group B and their respective teachers. First, for referral this study, observations were done in Portuguese Language classes, with the objective of verify how literacy practices have been developed by the teachers and how the students participate of them. It was found that both teachers and some students in their classes discussed about the mentioned texts, and after possible readings, they pointed their view. As for students, a few of them was engaged in set discussions. Then, it was analyzed the students’ writing productions, being chosen just 8 – 4 of each group. At this, through these productions, it was noted that these students placed / re-negociated their social identities (of gender and religious, according to main texts and speech genres worked in Portuguese Language classes). So, even if the effective number of students was not so large, those who participated, brought their writing productions and expressed themselves and their voices, based on one another voices, through social places where they live and the literacy practices which are developed in Portuguese Language classes. At last, the students re-negociate their social identities in writing productions.
Keywords: Letramento; Identidade; Produção textual; Práticas letradas; Literacy; Identidy; Literate Practices; Textual production; CNPQ::LINGUISTICA, LETRAS E ARTES::LETRAS